2017
DOI: 10.1002/1873-3468.12729
|View full text |Cite
|
Sign up to set email alerts
|

Conformational switch of harmonin, a submembrane scaffold protein of the hair cell mechanoelectrical transduction machinery

Abstract: Mutations in the gene encoding harmonin, a multi‐PDZ domain‐containing submembrane protein, cause Usher syndrome type 1 (congenital deafness and balance disorder, and early‐onset sight loss). The structure of the protein and biological activities of its three different classes of splice isoforms (a, b, and c) remain poorly understood. Combining biochemical and biophysical analyses, we show that harmonin‐a1 can switch between open and closed conformations through intramolecular binding of its C‐terminal PDZ‐bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…2 i) noncanonical protein–protein interactions, involved in the scaffolding function of HHDs together with the formation of intramolecular supramodules, as illustrated by the HHD-PDZ complex in Harmonin (Fig. 2 d) that tunes the binding affinity of the PDZ towards its partners [ 21 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 i) noncanonical protein–protein interactions, involved in the scaffolding function of HHDs together with the formation of intramolecular supramodules, as illustrated by the HHD-PDZ complex in Harmonin (Fig. 2 d) that tunes the binding affinity of the PDZ towards its partners [ 21 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the cochlea-specific exon68 of CDH23, which was shown to facilitate the dimerization of CDH23 CT, has the capacity to form large protein assemblies with USH1C (Wu et al, 2012). Both USH1C and USH1G were reported to have a tendency to self-associate and form oligomers (Bahloul et al, 2017;Yan et al, 2010;Yu et al, 2017). MYO7A, analogous to MYO6 (Yu et al, 2009), has been suggested to undergo cargo binding-induced dimerization (Sakai et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The αα-hub domains were recently defined based on a common structural foundation ( 21 ) and originally included the following domains: RCD1, SRO, and TAF4 (RST) from Radical-Induced Cell Death1 (RCD1) ( 21 ); paired amphipathic helix (PAH)1, PAH2, and PAH3 from Sin3 of the Sin3/histone deacetylase corepressor complex ( 25 ); TATA-box associated factor homology (TAFH) (or nervy homology region 1 [NHR1]) from transcription initiation factor TFIID-subunit 4 (TAF4) and eight-twenty-one (ETO) (or MTG8/CBFA2T1) ( 26 ); and nuclear coactivator binding domain (NCBD) (or IRF-binding domain) from CREB binding protein (CBP) ( 27 ) ( Figure 1 , Figure 2 , Figure 3 , A – D ). In addition, the harmonin homology domain (HHD) (or harmonin-N-terminal domain) from whirlin ( 28 ), harmonin ( 29 ), cerebral cavernous malformation 2 (CCM2) ( 30 ), and regulator of telomere elongation helicase 1 (RTEL1) ( 31 ) was assigned to the αα-hub domain group ( 24 ) ( Figs. 1 E and 2 E ).…”
Section: The αα-Hubsmentioning
confidence: 99%